Analisis Faktor-Faktor Yang Berhubungan Dengan Keterlambatan Klaim BPJS Di RSUD Sijunjung - Remi Famel; Hardisman Hardisman (Jurnal Mirai Management, 2023)
A hospital is an institution whose main function is to provide healthcare services to the public. Additionally, a hospital is a healthcare institution that provides comprehensive individual healthcare services by offering inpatient, outpatient, and emergency care. Comprehensive healthcare services refer to services that include promotive, preventive, curative, and rehabilitative actions. One of the government's efforts to provide healthcare services to the public is through implementing the National Health Insurance Program (JKN). The purpose of this research is to analyze the factors related to the delay in BPJS claims at RSUD Sijunjung. The method used is survey analysis or receptive survey. The sampling method employed is total sampling, where all 29 staff members are included as the sample population. The results indicate that there is a positive and significant correlation between the staff's knowledge and the delay in BPJS claims at RSUD Sijunjung. Similarly, there is a positive and significant correlation between education and the delay in BPJS claims at RSUD Sijunjung. Training also shows a positive and significant correlation with the delay in BPJS claims at RSUD Sijunjung. Moreover, work experience, human resources, attitude, completeness of documents, information technology, and facilities all demonstrate a positive and significant correlation with the delay in BPJS claims at RSUD Sijunjung. In conclusion, the knowledge of the staff, education level, training, work experience, human resources, attitude, completeness of documents, information technology, and facilities collectively have a positive and significant correlation with the delay in BPJS claims at RSUD Sijunjung. A claim is a request from one of the two parties bound by an agreement, seeking to have their rights fulfilled, and the party making the claim submits it to the other party in accordance with the agreed-upon agreement or policy provisions. Keywords: Pendidikan, Pelatihan, Pengalaman Kerja, SDM, Sikap